Analysis of Development Strategy Management of the Indonesian Navy Hospital dr. R. Oetojo - Satrio Sugiharto Machfudi; Wahyu Wijaya; Heri Iswanto (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2019)
This study aims to analyze the strategic management of the Sorong Naval Hospital dr. R. Oetojo, Indonesian Navy development in an effort to provide personnel health services in the Sorong XIV Main Naval Base working area. The scope of the study includes the analysis of external environmental factors that become opportunities and threats, and analysis of internal environmental factors that become strengths and weaknesses, redefining the vision and mission, setting long-term goals until 2023, determining alternative strategies and determining the chosen strategy appropriate. The research method is operational with a combination of research data from interviews and questionnaires. Implementation performance and quality of health services consisting of dimensions of tangible, reliability, responsiveness, assurance, and empathy with an average index of 4.00 or 80.15% have good results. The strategy was chosen by using the SWOT matrix and IE matrix to obtain the organization's position. Health services Naval Hospital dr. R. Oetojo, Indonesian Navy based on the SWOT matrix analysis is in quadrant I, which is an aggressive strategy which replaces with that has a very profitable position or strategy, maximizes opportunities and strengths, and supports aggressive growth policies. The results of the IE matrix obtained the total value of the EFAS matrix 3.159 and IFAS matrix 3.203, so that the hospital position is in the cell I or is described as Grow and Build with alternative strategies including market penetration, market development, and product development.